Asesinato en el kibbutz : un caso comunitario - Gur, Batya; Corniero, María; Gur, Batya (Madrid : Ediciones Siruela, 2012)
In a kibbutz in Israel, chief superintendent Michael Ohayon of the Serious Crime Unit investigates the murder of a beautiful woman killed by lethal insecticide. In part mystery, in part life on a kibbutz. By the author of Literary Murder.
Originally published in Hebrew and translated into English as Murder on a kibbutz.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Ohayon, Michael -- (Fictitious character) -- Fiction; Police -- Israel -- Fiction; Kibbutzim -- Fiction; Israel -- Fiction; Detective and mystery fiction; Electronic books